Functional roles of Ca(v)1.3 (alpha(1D)) calcium channel in sinoatrial nodes - Insight gained using gene-targeted null mutant mice - Zhang, Z; Xu, YF; Song, HT; Rodriguez, J; Tuteja, D; Namkung, Y; Shin, HS; Chiamvimonvat, N (LIPPINCOTT WILLIAMS & WILKINS, 2002)
We directly examined the role of the Ca(v)1.3 (alpha(1D)) Ca2+ channel in the sinoatrial (SA) node by using Ca(v)1.3 Ca2+ channel-deficient mice. A previous report has shown that the null mutant (Ca(v)1.3(-/-)) mice have sinus bradycardia with a prolonged PR interval. In the present study, we show that spontaneous action potentials recorded from the SA nodes show a significant decrease in the beating frequency and rate of diastolic depolarization in Ca(v)1.3(-/-) mice compared with their heterozygous (Ca(v)1.3(+/-)) or wild-type (WT, Ca(v)1.3(+/+)) littermates, suggesting that the deficit is intrinsic to the SA node. Whole-cell L-type Ca2+ currents (I(CaL)s) recorded in single isolated SA node cells from Ca(v)1.3(-/-) mice show a significant depolarization shift in the activation threshold. The voltage-dependent activation of Ca(v)1.2 (alpha(IC)) versus Ca(v)1.3 Ca2+ channel subunits was directly compared by using a heterologous expression system without 0 coexpression. Similar to the I-Ca.L recorded in the SA node of Ca(v)1.3(-/-) mutant mice, the Ca(v)1.2 Ca2+ channel shows a depolarization shift in the voltage-dependent activation compared with that in the Ca(v)1.3 Ca2+ channel. In summary, using gene-targeted deletion of the Ca(v)1.3 Ca2+ channel, we were able to establish a role for Ca(v)1.3 Ca2+ channels in the generation of the spontaneous action potential in SA node cells.
Keywords: BULLFROG SYMPATHETIC NEURONS; PANCREATIC BETA-CELLS; HEART-RATE REGULATION; CA2+ CHANNELS; PACEMAKER ACTIVITY; IONIC CURRENT; CALMODULIN; SUBUNIT; INACTIVATION; CLAMP